1993
DOI: 10.1113/expphysiol.1993.sp003677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of D‐glucose, L‐glucose and D‐mannitol on renal calcium handling and general renal function in the rat

Abstract: SUMMARYStandard renal clearance techniques were used to compare the effects of D-glucose, L-glucose and D-mannitol on renal calcium handling and general renal function in the anaesthetized rat. A significant (P < 0 01) calciuresis was seen in animals infused with D-glucose. This resulted from a decreased tubular reabsorption of calcium. A similar response was not seen with Lglucose or D-mannitol. The contrasting actions of the three sugars on tubular calcium transport may relate to their different transport ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…L-Glucose is not actively transported by mammalian cells and is eventually eliminated from the animal by renal clearance. 29 Six tumor bearing animals were studied to determine glycolytic rates of RIF-1 tumors obtained by fitting 13 C NMR data to our model (eq. 3).…”
Section: Methodsmentioning
confidence: 99%
“…L-Glucose is not actively transported by mammalian cells and is eventually eliminated from the animal by renal clearance. 29 Six tumor bearing animals were studied to determine glycolytic rates of RIF-1 tumors obtained by fitting 13 C NMR data to our model (eq. 3).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that glucagon increases GFR in adult dogs and humans but has no effect on the GFR of fetal sheep [47]. Contrariwise, L-glucose infusion in rats leads to a decrease in GFR, yet D-glucose has no effect [48]. Finally, serum IGF-1 concentrations not stimulating total body glucose disposal could affect renal hemodynamics, suggesting a direct role of IGF-1 receptor-mediated events independent of glucose metabolism [35].…”
Section: Discussionmentioning
confidence: 99%
“…Петлевые диуретики (фуросемид, пиретанид, торасемид, этакриновая кислота) блокируют Na-K-Cl котранспорт апикальной мембраны, и этим нивелируют движущую силу пассивной параклеточной абсорбции кальция с соответствующим повышением его экскреции. Выраженность натриуреза параллельна кальциурезу [2,6,30].…”
Section: мочегонные препаратыunclassified